Early Intravenous Infusion of Mesenchymal Stromal Cells Exerts a Tissue Source Age-Dependent Beneficial Effect on Neurovascular Integrity and Neurobehavioral Recovery After Traumatic Cervical Spinal Cord Injury. (26th March 2019) - Vawda, Reaz; Badner, Anna; Hong, James; Mikhail, Mirriam; Lakhani, Alam; Dragas, Rachel; Xhima, Kristiana; Barretto, Tanya; Librach, Clifford L.; Fehlings, Michael G.
Abstract : Localized vascular disruption after traumatic spinal cord injury (SCI) triggers a cascade of secondary events, including inflammation, gliosis, and scarring, that can further impact recovery. In addition to immunomodulatory and neurotrophic properties, mesenchymal stromal cells (MSCs) possess pericytic characteristics. These features make MSCs an ideal candidate for acute cell therapy targeting vascular disruption, which could reduce the severity of secondary injury, enhance tissue preservation and repair, and ultimately promote functional recovery. A moderately severe cervical clip compression/contusion injury was induced at C7-T1 in adult female rats, followed by an intravenous tail vein infusion 1 hour post-SCI of (a) term-birth human umbilical cord perivascular cells (HUCPVCs); (b) first-trimester human umbilical cord perivascular cells (FTM HUCPVCs); (c) adult bone marrow mesenchymal stem cells; or (d) vehicle control. Weekly behavioral testing was performed. Rats were sacrificed at 24 hours or 10 weeks post-SCI and immunohistochemistry and ultrasound imaging were performed. Both term and FTM HUCPVC-infused rats displayed improved ( p  < .05) grip strength compared with vehicle controls. However, only FTM HUCPVC-infusion led to significant weight gain. All cell infusion treatments resulted in reduced glial scarring ( p  < .05). Cell infusion also led to increased axonal, myelin, and vascular densities ( p  < .05). Although post-traumatic cavity volume was reduced with cell infusion, this did not reach significance. Taken together, we demonstrate selective long-term functional recovery alongside histological improvements with HUCPVC infusion in a clinically relevant model of cervical SCI. Our findings highlight the potential of these cells for acute therapeutic intervention after SCI. : Abstract : To evaluate the importance of tissue source age in the therapeutic efficacy of mesenchymal stromal cells (MSCs) for traumatic spinal cord injury, we compare human umbilical cord-derived cells of distinct ages (A). Following a clip compression injury model (at C7-T1), 2.5 million MSCs were injected intravenously via the tail vein (B). Acutely post-transplant, all cell types significantly reduced vascular permeability, parenchymal hemorrhage, and lesion volume (C). In long-term assessment, which involved weekly behavioral testing, both term and FTM HUCPVC-infused rats exclusively displayed improved ( p < .05) grip strength compared with vehicle controls (D). However, only FTM HUC PVC-infusion led to significant weight gain. While our findings highlight the potential of all these cells for acute therapeutic intervention after SCI, FTM-HUCPVC-infusion outperformed commercially available BMSCs, and conferred long-term functional recovery making it a prime candidate for further studies.